PENGARUH PENGELUARAN PEMERINTAH, INVESTASI SWASTA DAN PENYERAPAN TENAGA KERJA TERHADAP PERTUMBUHAN EKONOMI DI INDONESIAâ€ - B01112047, Nurma (Jurnal Curvanomic, 2016)
High economic growth indicates the success of regional development. It is expected that economic development enable to enhance production factors, the ones which elicit big scheme economic development. This study aims to investigate how much influence of government expenditure, private investment, and employment to economic growth in Indonesia. This qualitative study uses panel data analysis to examine five year secondary data (2010-2014) from 33 provinces in Indonesia. The model of analysis used is multiple linear regression with fixed effects. The result show that (1) government expenditure (prob. 0.0000) and private investment (prob. 0.0009) affect positive and significantly to the economic growth. However, employment (prob. 0.4215) has positive but not significant contribution to the growth. It can be established from R2 level (0.983893) 0R 98.39 percent of dependent variables wich contribute to economic development in Indonesia.Key words: economic growth, government expenditure, private investment, employment